Intraoperative identification of the corticospinal tract and dorsal column of the spinal cord by electrical stimulation. Issue 7 (7th February 2018) - Deletis, Vedran; Seidel, Kathleen; Sala, Francesco; Raabe, Andreas; Chudy, Darko; Beck, Juergen; Kothbauer, Karl F
Abstract : Objectives: Anatomical identification of the corticospinal tract (CT) and the dorsal column (DC) of the exposed spinal cord is difficult when anatomical landmarks are distorted by tumour growth. Neurophysiological identification is complicated by the fact that direct stimulation of the DC may result in muscle motor responses due to the centrally activated H-reflex. This study aims to provide a technique for intraoperative neurophysiological differentiation between CT and DC in the exposed spinal cord. Methods: Recordings were obtained from 32 consecutive patients undergoing spinal cord tumour surgery from July 2015 to March 2017. A double train stimulation paradigm with an intertrain interval of 60 ms was devised with recording of responses from limb muscles. Results: In non-spastic patients (55% of cohort) an identical second response was noted following the first CT response, but the second response was absent after DC stimulation. In patients with pre-existing spasticity (45%), CT stimulation again resulted in two identical responses, whereas DC stimulation generated a second response that differed substantially from the first one. The recovery times of interneurons in the spinal cord grey matter were much shorter for the CT than those for the DC. Therefore, when a second stimulus train was applied 60 ms after the first, the CT-fibre interneurons had already recovered ready to generate a second response, whereas the DC interneurons were still in the refractory period. Conclusions: Mapping of the spinal cord using double train stimulation allows neurophysiological distinction of CT from DC pathways during spinal cord surgery in patients with and without pre-existing spasticity.